A migratory divide spanning two continents is associated with genomic and ecological divergence. (23rd February 2022) - Turbek, Sheela P.; Schield, Drew R.; Scordato, Elizabeth S. C.; Contina, Andrea; Da, Xin‐Wei; Liu, Yang; Liu, Yu; Pagani‐Núñez, Emilio; Ren, Qing‐Miao; Smith, Chris C. R.; Stricker, Craig A.; Wunder, Michael; et al.
Abstract: Migratory divides are contact zones between breeding populations with divergent migratory strategies during the nonbreeding season. These locations provide an opportunity to evaluate the role of seasonal migration in the maintenance of reproductive isolation, particularly the relationship between population structure and features associated with distinct migratory strategies. We combine light‐level geolocators, genomic sequencing, and stable isotopes to investigate the timing of migration and migratory routes of individuals breeding on either side of a migratory divide coinciding with genomic differentiation across a hybrid zone between barn swallow ( Hirundo rustica ) subspecies in China. Individuals west of the hybrid zone, with H. r. rustica ancestry, had comparatively enriched stable‐carbon and hydrogen isotope values and overwintered in eastern Africa, whereas birds east of the hybrid zone, with H. r. gutturalis ancestry, had depleted isotope values and migrated to southern India. The two subspecies took divergent migratory routes around the high‐altitude Karakoram Range and arrived on the breeding grounds over 3 weeks apart. These results indicate that assortative mating by timing of arrival and/or selection against hybrids with intermediate migratory traits may maintain reproductive isolation between the subspecies, and that inhospitable geographic features may have contributed to the diversification of Asian avifauna by influencing migratory patterns.